The Influence of Audio Visual Media on Critical Thinking in Civics Learning for Islamic Elementary School - Insani, Fitrah; Dahlan, Zaini (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research examines the effect of using audio-visual media on critical thinking in Civics learning in class V Min 4 students in Medan City. This research is quantitative research using experimental research methods. The population used in this research was all classes V Min 4 in Medan City for the 2023/2024 academic year, totaling 108 students. The sampling technique that researchers will use is nonprobability sampling, the Purposive sampling model. The sample in this research was 21 class VA students and 18 class VB students. They were collecting research data through interviews, observation, documentation, and Testing, collecting research data, interviews, observation, and documentation and using a 5 question Essay Test for critical thinking skills. The inferential statistical technique used is prerequisite analysis for normality tests, homogeneity tests, and independent t-tests to test hypotheses. Based on the research results, there are differences in students' average critical thinking learning outcomes in the control and experimental classes, which shows the influence of audio-visual media on critical thinking in civics learning. Based on the criteria for the effectiveness of using audio-visual media on students' critical thinking, they are at the third level. or effective enough to be used in learning.